The role of physical activity in the proper development of a child in preschool age - Michał Kowalewski (Kazimierz Wielki University, 2020)
This article aims to pay special attention to the role of physical activity in the proper development of a preschool child, both physically, mentally and socially. It emphasizes the special role of motor games in shaping motor skills, also needed at the next stage of education, at school, as well as the appropriate preparation of teachers to conduct motor activities in preschool education.